Chondrichthyan fishes in the Arctic Ocean and adjacent seas - do we know our species? - Lynghammar, Arve (UiT The Arctic University of Norway, 2014)
The papers of the thesis are not available in Munin: 1. Lynghammar, A., Christiansen, J.S., Mecklenburg, C.W., Karamushko, O.V., Møller, P.R. & Gallucci, V.F.: 'Species richness and distribution of chondrichthyan fishes in the Arctic Ocean and adjacent seas', Biodiversity 14(1): 57-66 (2013). Available at http://dx.doi.org/10.1080/14888386.2012.706198 2. Lynghammar, A., Christiansen, J.S., Griffiths, A.M., Fevolden, S-E., Hop, H. & Bakken, T.: 'DNA barcoding of the northern Northeast Atlantic skates (Chondrichthyes, Rajidae), with remarks on the widely distributed starry ray', Zoologica Scripta Volume 43, Issue 5, published online: 23 June 2014. Available at http://dx.doi.org/10.1111/zsc.12064 3. Lynghammar, A., Præbel, K., Fevolden, S-E. & Christiansen, J.S., 'Population genetic structure of an abundant skate (Amblyraja radiata) in the North Atlantic Ocean.' Manuscript The basal prerequisite for managing species and understanding ecosystems is correct species and population identification. Without knowing the species, we cannot with accuracy detect changes in distribution or abundance due to climate change, fisheries, diseases or any other types of impact. This thesis gives the first complete overview of chondrichthyan fishes (sharks, skates, rays and chimaeras), recorded in the Arctic Ocean and adjacent seas. A total of 49 species were found to occur, and the most specious regions were the Bering Sea, the Norwegian Sea and the Barents Sea, also known as the Arctic Gateways. The Bering Strait is an effective zoogeographic barrier, separating the Pacific from the Atlantic species. In particular, skates are prone to misidentifications. Species complexes are known to occur, and the group is commonly lumped as “Skates & Rays” in fishery statistics or in scientific publications. By use of genetic methods (DNA barcoding), the skate species reported from the northern Northeast (nNE) Atlantic was investigated. A total of 12 species were found to occur in the area, and three of those were new for the ...